PATIENT SATISFACTION WITH KNEE ARTHROSCOPY UNDER LOCAL ANAESTHESIA - Iqbal, Malik Javed; Inam, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the level of patients' satisfaction with knee arthroscopy under local anaesthesia. Material and Methods: This descriptive study was conducted in a private hospital setup from 2004 to 2008 on 30 consecutive patients who had knee arthroscopy under local anaesthesia. Bupivacaine (150 milligrams) was injected into the knee joint and lignocaine with adrenalin injected into skin portals. Intravenous sedation was also given to some anxious patients during the procedure. At first follow up visit we evaluated level of satisfaction in quarters 25, 50, 75 and 100% by parameters pain, anxiety, theater environment, recommendation of the same procedure to friends and overall experience about procedure. Results: Three (10%) patients were 100 % satisfied, 20 (66.7%) patients were 75% satisfied, 5 (16.7%) patients were 50% satisfied and 2 (6.6%) patients were 25% satisfied. The overall satisfaction rate was 70%. Ten (33.3%) patients reported no pain, 19 (63.4%) reported mild pain and 1(3.3%) reported moderate degree of pain. Twenty four (80%) patients were anxious during the procedure. Twenty seven (90%) patients reported that the theater environment was not friendly. Twenty one (70%) patients recommended the same procedure to friends. The experience about the procedure was excellent in five (16.7%) patients, good in 24 (80%) and fair in 1 (3.3%) patient. Cocnlsuion: When patients are properly counseled and their anxiety alleviated; knee arthroscopy under local anaesthesia is well tolerated procedure.